Strategies in Teaching Speaking used by Teachers of Young, Junior High School, Senior High School, and University Students - Heidy Wulandari (Universitas Dian Nuswantoro, 2020)
Abstract. This study aims at describing strategies in teaching speaking adopted by teachers of different student levels. The method used was descriptive qualitative method with 32 participants. The instrument was interview in the form of focused group discussion. The data were analyzed using open coding and categorization. The result shows that teachers of all levels tend to consider students’ needs, the components of teaching speaking, and the media. For young learners, the teachers use discussion, story-telling, speech, guessing game, problem solving, and simulation. Games, modeling, electronic media, and instruction are suggested by the teachers as additional strategies. Meanwhile the strategies used for teaching speaking to junior high school students are discussion, story-telling, guessing game, and role play. Direct speaking is suggested as additional strategy. Moreover for teaching speaking to senior high school students, the teachers choose strategies such as discussion, story-telling, speech, guessing game, role play, problem solving, simulation, information gap, and jigsaw. Additional strategies suggested by the teachers are building sentences from root, talking stick, team game tournament, think pair and share, snowball throwing game, think, discuss and share, talking English directly, give and take model, time token model, repeat pronouncing words, and media and teacher as model. Then for teaching speaking to university students, the strategies chosen are role play, discussion, story-telling, problem solving, speech and simulation, guessing game, and information gaps. The additional strategies suggested by the teachers are hot seat and presentation. Finally, it is recommended that the further research will take time limitation, and the strategies strengths and weaknesses into account. Keywords: speaking, strategies, teaching Abstrak. Penelitian ini bertujuan untuk mendeskripsikan tentang strategi mengajar berbicara bahasa Inggris yang dipakai guru dalam mengajar siswa dengan level berbeda. Metode yang digunakan adalah metode kualitatif deskriptif dengan 32 partisipan. Instrumen yang digunakan adalah wawancara dalam bentuk fokus grup diskusi. Analisis data dilakukan dengan koding dan kategorisasi. Hasil analisa menunjukkan bahwa guru cenderung mempertimbangkan kebutuhan siswa, komponen dalam mengajar speaking, dan media. Untuk mengajar anak-anak guru menggunakan strategi diskusi, bercerita, berpidato, tebak-tebakan, penyelesaian masalah, dan simulasi. Permainan, model, media elektronik dan instruksi disarankan oleh para guru sebagai strategi tambahan. Sementara itu untuk mengajar berbicara bahasa Inggris pada siswa SMP, strategi yang digunakan adalah diskusi, bercerita, tebak-tebakan, dan bermain peran. Berbicara langsung disarankan sebagai strategi tambahan. Selain itu, untuk mengajar berbicara bahasa Inggris pada siswa SMA, guru memilih strategi seperti diskusi, bercerita, pidato, tebak-tebakan, bermain peran, penyelesaian masalah, simulasi, gap informasi ,dan jigsaw. Strategi tambahan yang disarankan oleh para guru adalah membuat kalimat dari akar kata, tongkat berbicara, turnamen tim, berpikir, berpasangan, dan berbagi, lempar bola salju, berpikir, berdiskusi, dan berbagi, berbicara langsung bahasa Inggris, memberi dan menerima, model token waktu, dan mengucapkan kata berulang. Kemudian untuk mengajar mahasiswa, strategi yang dipilih adalah bermain peran, diskusi, bercerita, penyelesaian masalah, berpidato dan simulasi, tebak-tebakan, dan gap informasi. Strategi tambahan yang disarankan oleh para guru adalah kursi panas dan presentasi. Penelitian ini tidak mempertimbangkan kekurangan dan kelebihan dari setiap strategi. Oleh karena itu aspek kekurangan dan kelebihan dari strategi mengajar speaking di level berbeda sangat direkomendasikan bagi penelitian selanjutnya. Kata kunci: berbicara bahasa Inggris, mengajar, strategi